The European Green Deal: more than an exit strategy to the pandemic crisis, a building block of a sustainable European economic model - Bongardt, Annette (2022)
This article puts forward that the European Green Deal (EGD) is more than just another initiative for green growth. Instead, it adds a building block to the European economic model, alongside the single market and economic and monetary union. The pandemic crisis would therefore need to be addressed also through the EGD framework. We find that the Covid-19 crisis provided a missing link between the EGD's long-term objectives and conducive short-term policies. We discuss to what extent economic governance changes reinforce the role of the EGD as a pillar of the European Union economic model, contributing also to creating strong (political, institutional and society) dynamics in favour of sustainability and promoting integration.